1975
DOI: 10.1002/ange.19750871116
|View full text |Cite
|
Sign up to set email alerts
|

Aziridinimine, Diaziridinimine, Diaziridinone und Carbodiimide durch Photolyse von 2‐Tetrazolinen

Abstract: gen) entwickelten Filmwaage bei konstanter Spreitflache ein Schub-Zeitdiagramm auf, so ermittelt man fur (2) den Spreitungsdruck p= 28.5 und fiir ( I ) nur 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1977
1977
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The photochemically induced opening of the tetrazole ring has been found to be an easy process. , As mentioned in the Introduction, tetrazole itself easily eliminates molecular nitrogen, leading to production of nitrilimine, which then undergoes secondary photoreactions, such as isomerization to carbodiimide, cyanamide, or a hydrogen cyanide/nitrene complex . In the case of 2MTA, the weakest bonds of the tetrazole ring are N1−N2, N2−N3, and N4−C5, which correspond to the formal single bonds and can then be expected to undergo easier photochemical cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…The photochemically induced opening of the tetrazole ring has been found to be an easy process. , As mentioned in the Introduction, tetrazole itself easily eliminates molecular nitrogen, leading to production of nitrilimine, which then undergoes secondary photoreactions, such as isomerization to carbodiimide, cyanamide, or a hydrogen cyanide/nitrene complex . In the case of 2MTA, the weakest bonds of the tetrazole ring are N1−N2, N2−N3, and N4−C5, which correspond to the formal single bonds and can then be expected to undergo easier photochemical cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…Outlined below are the results of our initial foray into this promising territory, with emphasis on the coordination chemistry of gold as a particularly "carbophilic" and catalytically relevant Lewis acid. [5,6] Although compound 1 has been investigated in some detail, [2,3,7] the parent 1,3-dimethyl-2-methyleneimidazoline (3) itself has not been isolated in pure form. Gratifyingly, we found that this particular compound is readily obtained as an air-sensitive solid by deprotonation of imidazolium iodide 2 with KH in Et 2 O (Scheme 2).…”
mentioning
confidence: 99%
“…C 60.52 H 10.87 N 20.58 b) Man ruhrte 20 rng (0.07 mmol) 14b und 22 mg (0.15 mmol) Caesiumfluorid 0.5 h in 0.6 ml [D3]Acetonitril bei 2 0 -2 5 T , filtrierte und erhielt quantitativ 14a ('H-NMR). [1][2][3][4][5][6][7][8][9][10][11][12]2,: Nach der Vorschrift fur 14a aus 11 mmol 13'5' und 16 ml einer 0.76 M Losung von [(Trimethyl-~ilyl)methyl]lithium~~) in Pentan (12 mmol 12,2, ( N-(2,2-Dimethylpropyl~-2,2-dimethyl-l-c und der Fehler von (kE + kZ) dienten zur Berechnung der angegebenen Fehler von kE und k,.…”
Section: Photolyse Und Thermolyse Des Dihydroj-methylen-123-triazolunclassified